1978
DOI: 10.1029/jb083ib05p02273
|View full text |Cite
|
Sign up to set email alerts
|

Seismic properties of a shallow magma reservoir in Kilauea Iki by active and passive experiments

Abstract: The use of multiple methods is essential for determination of seismic properties of a complex structure like a partially frozen lava pond. In our experiment with Kilauea Iki during March 1976 (1) the spatial distribution of seismic events originating from the crust best defined the lateral location of the magma lens, (2) the S waves transmitted through the magma lens and dispersion of Love waves generated by explosive sources in the Iki floor constrained the S wave velocity structure, and (3) P waves from expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1979
1979
2004
2004

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…Concurrently with these theoretical advances, AKI et al (1978) conducted a series of key field experiments at Kilauea Iki, Hawaii, in which they demonstrated that the use of multiple seismic methods is essential for a determination of a complex seismic structure such as found in a cooling, partially solidified basaltic lava lake (RICHTER and MOORE, 1966;RICHTER et al, 1970;HELZ, 1993;BARTH et al, 1994). In active and passive experiments conducted at Kilauea Iki, Aki and associates used a combination of P waves and surface waves from explosions detonated in the lake crust to determine the velocity structure of the lava lake, relied on teleseismic S waves transmitted through the residual lens of melt to further constrain the shear velocity structure, and obtained an estimate of the lateral dimensions of the still-molten magma lens from the spatial distribution of seismic events originating within the cooling crust.…”
Section: Introductionmentioning
confidence: 90%
“…Concurrently with these theoretical advances, AKI et al (1978) conducted a series of key field experiments at Kilauea Iki, Hawaii, in which they demonstrated that the use of multiple seismic methods is essential for a determination of a complex seismic structure such as found in a cooling, partially solidified basaltic lava lake (RICHTER and MOORE, 1966;RICHTER et al, 1970;HELZ, 1993;BARTH et al, 1994). In active and passive experiments conducted at Kilauea Iki, Aki and associates used a combination of P waves and surface waves from explosions detonated in the lake crust to determine the velocity structure of the lava lake, relied on teleseismic S waves transmitted through the residual lens of melt to further constrain the shear velocity structure, and obtained an estimate of the lateral dimensions of the still-molten magma lens from the spatial distribution of seismic events originating within the cooling crust.…”
Section: Introductionmentioning
confidence: 90%
“…Which rheological model should we choose for the range of seismic frequencies in volcanic media? Are there any S waves in the magma as a partially crystallized body, or when do they appear (Aki et al 1978)? What is the effect of the anelastic rheology on the wave dispersion of low‐frequency earthquakes?…”
Section: Attenuation and Dispersion Of Seismic Waves In Volcanic Mediamentioning
confidence: 99%
“…The detection and characterization of magma bodies in the crust and upper mantle has been a long-standing goal in seismology, and a topic of interest for Kei Aki throughout his career (e.g., AKI, 1968;AKI et al, 1978;ROBERTS, AKI, and FEHLER, 1991). Early studies of magma bodies were often based on the fortuitous observation of ''exotic'' phases within waveforms recorded in volcanic regions (PEPPIN, 1987).…”
Section: Introductionmentioning
confidence: 99%